MANAJEMEN KEUANGAN DAN PERILAKU MENABUNG PADA MAHASISWA FAKULTAS PERTANIAN UNIVERSITAS UDAYANA - Ni Nyoman Febri Wulandari; Gede Mekse Korri Arisena (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
Understudies, a piece of the informed local area, play a significant part in financial development, one of which is saving. This study aims to identify student characteristics, examine the application of financial management and saving behaviors among Agriculture Faculty students at Udayana University, and investigate the connection between the two. The sample of this research is 94 people with proportional random sampling. The data analysis method used is descriptive qualitative, quantitative, and Pearson's Product Moment. The research results show that: 1). Characteristics of students based on the age of majority is 20 years, based on gender are women, and most are in the agribusiness study program. Most of the students came from Bali and North Sumatra, where most of them chose boarding houses. Students tend to be unmarried and have dependents. The work of student parents is dominated by private employees. The biggest source of income for students is from their parents. The most preferred place to save is the bank. 2). The application of financial management and saving behavior to students is good. 3). There is a positive and unidirectional relationship between the application of financial management and saving behavior among students.